Techno-economics of algae production in the Arabian Peninsula - Kira Schipper (17316883) (2021)
The Arabian Peninsula’s advantageous climate, availability of non-arable land, access to seawater and CO2-rich flue gas, make it an attractive location for microalgae biomass production. Despite these promising aspects, the region has seen very few studies into the commercial feasibility of algae-based value chains. This work aims to address this gap through a techno-economic feasibility study of algae biomass production costs, comparing different photobioreactor types, locations, and production scales. Flat panel and raceway pond cultivation systems were found to be the most economically attractive cultivation systems, with biomass production costs as low as 2.9 €·kg−1. Potential cost reductions of up to 42.5% and 25% could be accomplished with improvements in photosynthetic efficiencies and increased culture temperatures, respectively. As of such, efforts to source local thermo- and photo- tolerant strains could be the key to unlock the potential of the region for algae commercialization, linking into food, feed and nutraceutical industries. Other Information Published in: Bioresource Technology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.biortech.2021.125043